Benign Prostatic Hyperplasia (BPH): A Comprehensive Analysis of the Malaise and Summarizing Possible Management Options through Phytotherapeutic Agents - Sasidharan, Shan; Srinivasakumar, Kumarapillai Parameswaran; Poddar, Sandeep; Bhaumik, Amiya; Das, Sreemoy Kanti; J, Hareendran Nair (Kesmas, 2022)
Benign prostatic hyperplasia (BPH) is a severe illness affecting middle-aged and geriatric male patients. This disease normally occurs at the age of 40 or above and is also associated with sexual dysfunction. Alpha-blockers and 5α-reductase inhibitors are the preferred drugs practiced to treat BPH. However, invasive surgical therapy remains the gold standard for managing the condition in the case of refractory and intricate BPH conditions. Due to the fear of sexual dysfunction and the detrimental influence on their quality of life, most patients seek to avoid synthetic drugs and surgery. For this reason, several patients turn to phytotherapy and other alternative therapies. The authors looked at the existing perceptions of epidemiology, etiology, and pathophysiology associated with BPH in this review article. In addition, this article contained basic information on the pathological roles of inflammation in BPH and various diagnoses and treatment options. It was well reported that the administration of medicinal herbs played a vital role in managing BPH. In recent years, many researchers worldwide have reported the efficiency and safety of phytochemicals in managing numerous pathological disorders in-vivo and in-vitro conditions and the prevention of illness.